FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMEN BUAH IMPOR - Sudiyarto Sudiyarto; Ramdan Hidayat; Sri Widayanti (University of Jember, 2007)
Consumers hold important role in determination whether the product has superiority or not. The overflowing or import fruits affected to a strong competition between local and impor fruits. Although local fruit seemingly lost in the competing with import fruits, however the consumer (especially city consumer) is the final determiner who act the jury to judge the kind of fruit that is superior through multi attribute judgement. The research objected was to analyze the influece of the factors namely culture, social enviroment, individual, psychological and marketing strategy toward consumer’s attitude in purchasing fruits to show ‘competitive value’ of local fruit toward impor fruits. This research purposely conducted in Surabaya as one of the final destinations for fruit marketing with fruit’s consumer as a respondent and using survey method. Sample taken of 140 responden from five Surabaya areas. Data collection conducted by interviews and direct obsevation toward several research object. This research analyzed by Structural Equation Modelling (SEM). The result shows that on import fruits, changing culture and the increasing of individual characteristic significally significant effect to consumer behaviour in import fruits consumtion. Furthermore, the consumer achievement behaviour statistically significant support to vendor to take “marketing strategi” Keywords : Consumer Behaviour, Import fruits, Structural Equation Modelling